2018
DOI: 10.1007/s11255-018-1946-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the plasma endocan level a reliable predictor for the severity of erectile dysfunction?

Abstract: This study demonstrated the presence of an association between plasma endocan levels and ED. Endocan may be used as a new diagnostic marker for the severity of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The Sexual Health Inventory for Men Score was also shown to have a high negative correlation with endocan levels. This investigation confirmed that there is a correlation between plasma endocan levels and erectile dysfunction [38].…”
Section: Endocansupporting
confidence: 82%
See 1 more Smart Citation
“…The Sexual Health Inventory for Men Score was also shown to have a high negative correlation with endocan levels. This investigation confirmed that there is a correlation between plasma endocan levels and erectile dysfunction [38].…”
Section: Endocansupporting
confidence: 82%
“…Serum endocan levels differed significantly between individuals with and without severe erectile dysfunction, according to research by Onuk et al (2018). The Sexual Health Inventory for Men Score was also shown to have a high negative correlation with endocan levels.…”
Section: Endocanmentioning
confidence: 93%
“…In this context, CRP, a well-established inflammatory biomarker is strongly, independently associated with the ED (Li et al, 2019). Onuk et al (2018) classified the ED patients (as severe, moderate, or mild) using the Sexual Health Inventory for Men (SHIM) questionnaire. They reported a significant difference in serum endocan levels between the severe ED and the control group.…”
Section: Endocan and Erectile Dysfunctionmentioning
confidence: 99%
“…Endocan is a novel marker of endothelial dysfunction, inflammation and atherosclerosis. Raised circulating endocan levels were reported in some cardiovascular diseases and related conditions [4].…”
Section: Introductionmentioning
confidence: 99%